SUMBER TAFSIR AL-MA‘ṠUR DAN AL-RA’YU SERTA PENGARUHNYA TERHADAP KARYA TAFSIR KONTEMPORER - Ahmad Dani Saleng; Achmad Abubakar; Sohrah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
This study seeks to provide an explanation of the sources of al-ma’ṡur and al-ra'yu in an interpretation as well as to analyze the influence of these two sources on contemporary exegetical works. This research is a literature study using content analysis techniques in processing the data obtained. The results of this study are that the source of al-ma’ṡur is a source of interpretation based on history, while the source of al-ra'yu is based on thought. The form of interpretation with the source of al-ma’ṡur can be in the form of interpretation of verses from the Koran, hadith, the opinion of friends and tabi'in, while the form of interpretation with the source of al-ra'yu is in the form of interpretation of verses based on the results of the mufasir's thoughts by relying on various aspects and point of view. The source of al-ra'yu is more widely used in contemporary works than the source of al-ma’ṡur. This is because the source of al-ra'yu is considered by contemporary interpreters to be very suitable for producing interpretations of verses that are in accordance with the times.